Hubungan Pendidikan Agama Islam Dengan Tingkat Religiusitas - wiwinda wiwinda (Institut Agama Islam Negeri Bengkulu, 2016)
Islamic education is the physical and spiritual guidance based on religious laws of Islam towards the establishment of a major personality dimensions according to Islam. Arifin, said Islamic religious education is an attempt to nurture the students to always be able to understand the teachings of Islam as a whole. Deeds of one's actions in daily life are not only seen from one dimension alone, but covers all the beliefs, worship, appreciation, religious knowledge and experience, all of which must relate to one another. Because every Muslim in thinking and acting being ordered according to the teachings of Islam in conducting economic activities, social, political or any activity Muslims are commanded to do so in order to worship Allah so that they act perfectly.